Model answers for Yes/No questions from EFL students in public senior high schools - I Wayan Dirgeyasa (Studies in English Language and Education, 2017)
This research aims to find out the typical categories of answers to Yes/No questions most used by students at selected Public Senior High Schools in Medan, Indonesia. These schools were classified into top favorite, medium favorite and non-favorite schools. Through a stratified clustered random sampling technique, six schools were chosen consisting of two schools from each classification. A number of 40 students were chosen from three class X, three class XI and three class XII at each of the six chosen schools, making a total sample of 720 students with 360 sets of dialogue scripts. Data was collected through documentation-recording dialogues. The data was transcribed and analyzed by descriptive analysis. The results of the research showed that: 1) the categories of the students’ answers to the Yes/No questions were distributed variously in terms of the six models. However, the distribution of the answers was not proportionally equal amongst all the models, 2) the dominant distribution of the answers was the third model with the formula Yes/No+additional information such as confirming, supporting, etc., reaching 37% of the total answers, whilst the least common models were the sixth and fourth categories respectively, which had 1% and 3% of the answers respectively, and finally 3) there was no significant difference in the distribution of the students’ answers in terms of the class of school whether top favorite, medium favorite or non-favorite. In conclusion, the ways to answer Yes/No questions need to be developed amongst students by their teachers by teaching and learning using natural, real life-like situations and in contextual ways.